Proceedings of the 53rd Annual Meeting of the Association for Computational Linguistics and the 7th International Joint Confere 2015
DOI: 10.3115/v1/p15-2123
|View full text |Cite
|
Sign up to set email alerts
|

Lifelong Learning for Sentiment Classification

Abstract: This paper proposes a novel lifelong learning (LL) approach to sentiment classification. LL mimics the human continuous learning process, i.e., retaining the knowledge learned from past tasks and use it to help future learning. In this paper, we first discuss LL in general and then LL for sentiment classification in particular. The proposed LL approach adopts a Bayesian optimization framework based on stochastic gradient descent. Our experimental results show that the proposed method outperforms baseline metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
132
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(134 citation statements)
references
References 24 publications
0
132
0
2
Order By: Relevance
“…Consequently, the concept of lifelong learning can hold realistic significance in long-term real-world applications. The concept of lifelong machine learning [106,265,266] is directed towards the construction of a model that can perform the retraining process repeatedly for the learning of new emerging patterns related to each behaviour. The model should be able to adapt to and learn from new environments continuously [106,265,266].…”
Section: ) Lifelong Learning For Learning Iot Threatsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the concept of lifelong learning can hold realistic significance in long-term real-world applications. The concept of lifelong machine learning [106,265,266] is directed towards the construction of a model that can perform the retraining process repeatedly for the learning of new emerging patterns related to each behaviour. The model should be able to adapt to and learn from new environments continuously [106,265,266].…”
Section: ) Lifelong Learning For Learning Iot Threatsmentioning
confidence: 99%
“…The concept of lifelong machine learning [106,265,266] is directed towards the construction of a model that can perform the retraining process repeatedly for the learning of new emerging patterns related to each behaviour. The model should be able to adapt to and learn from new environments continuously [106,265,266]. Researchers have reported that the further they trained the algorithm with the latest features of known DDoS attacks, the more they improved the detection probabilities for known and unknown DDoS attacks.…”
Section: ) Lifelong Learning For Learning Iot Threatsmentioning
confidence: 99%
“…Both concepts focus on the continuous learning processes for evolving tasks. However, sequential/online transfer learning emphasizes on how to improve the target domain performance (without sufficient target training data), but lifelong learning tries to improve the future target task (with sufficient target training data) as well as all the past tasks [28]. Also, the lifelong learning can be seen as incremental/online multi-task learning.…”
Section: Sequential/online Labelled Target Datamentioning
confidence: 99%
“…Never-ending learning is a rather general setup that defines how machines can learn like humans to transfer experience to different tasks in a self-supervised manner, and has been realized in a system for accumulating beliefs by reading continuously from the web [9]. Life-long learning [10], [11], on the other hand, considers feeding the machines with a sequence of tasks with the hope of improving the performance on the next task in the sequence. The setup is similar to our thought but has been realized on only sentiment classification tasks [10].…”
Section: Introductionmentioning
confidence: 99%